Medical students' adoption and evaluation of a completely digital general practice clerkship – cross-sectional survey and cohort comparison with face-to-face teaching. Issue 1 (31st December 2022) - Fehl, Marina; Gehres, Vera; Geier, Anne-Kathrin; Mundt, Thomas; Klinge, Kay; Frese, Thomas; Bleckwenn, Markus; Deutsch, Tobias
ABSTRACT: Background: During the COVID-19 pandemic, the University of Leipzig completely switched to online teaching. Thus, we developed a practice-oriented digital substitute for a two-week mandatory general practice (GP) clerkship. Main components were processing of clinical cases and additional GP topics, visual diagnoses, information and examination videos, and regular remote exchanges with associated GP teachers. We took the chance to comprehensively evaluate the new teaching formats (acceptance, use, working enjoyment, learning gain, practical relevance, insights into general practice) and to compare evaluations with two previous semesters to gain insights for future blended learning concepts. Methods: Cross-sectional post-hoc online evaluation among fourth year (of six) medical students participating in the digital mandatory 2-week GP clerkship during summer semester 2020; additional cohort comparison with two previous semesters (face-to-face clerkship). Results: Out of 192 participants in the digital clerkship, 99 completed our questionnaire (response rate = 51.6%). Results were compared with 277 previous evaluations (face-to-face semesters). Most participants reported having enjoyed the online-based clerkship (87.9%), having learned a lot (89.9%), having gained insights into general practice (76.8%), and perceived high practical relevance (90.9%). Implementing the new teaching formats into future face-to-face clerkships was welcomed by 65.6%. Clinical cases, visual diagnoses, examination videos and communication with GP teachers were rated best regarding working enjoyment, learning gain, practical relevance and insights into a GP's work. Cohort comparison revealed somewhat better evaluations regarding knowledge transfer for the digital clerkship while imparting of skills and attitudes was reportedly worse. Conclusions: Students welcomed the digital content and perceived relevant learning gain. Our results may help to develop future blended learning concepts. Clinical cases, examination videos and visual diagnoses appear to be particularly suitable as useful online complements which could enrich face-to-face teaching. As students especially valued the exclusive time for exchanges with their preceptor, this should be facilitated in face-to-face clerkships.